Design and implementation of a security system based on ADSL access technology. (September 2020) - Zhao, Qiuying; He, Huiwen; Chuai, Yunzhi; Huang, Hui; Huang, Yinan
Abstract: Taking the network switching equipment and the microcontroller as the core, a security system based on ADSL access technology is designed with the embedded method. The structure and communication mode of the security system are studied from three aspects: network switching equipment configurations, network communication module design of uplink equipment and communication module design of ADSL access equipment. The system can establish security monitoring points on existing telephone lines, which can not only meet the security protection requirements of high bandwidth, long transmission distance and information security, but can also reach the level of several kilometres. Furthermore, it can greatly reduce construction costs and operation costs of security system, and effectively realize the logistic support ability of security system.